Long-term Assessment of Systemic Inflammation and the Cumulative Incidence of Age-related Hearing Impairment in the Epidemiology of Hearing Loss Study - Nash, Scott D. (Oxford University Press, 2014)
BACKGROUND. Although research has linked systemic inflammation to various diseases of aging, few studies have examined the potential role it may play in the development of age-related hearing impairment. METHODS. Among 1,073 participants free of hearing impairment (pure-tone average 0.5, 1, 2, 4kHz ≤ 25 dB HL) in the population-based Epidemiology of Hearing Loss Study (1998–2000), serum C-reactive protein, and interleukin-6 were measured at three time points (1988–1990, 1998–2000, and 2009–2010), and tumor necrosis factor-α was measured at one time point (1998–2000), whereas hearing impairment was measured again in 2003–2005 and 2009–2010 to determine the 10-year cumulative incidence. RESULTS. Inflammatory marker levels from a single time point (1998–2000) were not associated with an increased risk of developing hearing impairment. Associations between long-term serum C-reactive protein levels and incident hearing impairment differed by age (p = .031). Participants less than 60 years with consistently high (>3 mg/L) or increasing levels of serum C-reactive protein over 10 years were nearly two times (hazard ratio: 1.96, 95% confidence interval: 1.19, 3.23) as likely to develop hearing impairment over the subsequent 10-year period, an association not seen in participants more than or equal to 60 years. A statistically significant association (p-trend = .041) was also observed between number of markers in the highest group at baseline and incident hearing impairment in this younger age group. CONCLUSIONS. Associations between long-term serum C-reactive protein levels and incident hearing impairment were observed in the cohort as a whole, but differed significantly by age group, with statistically significant associations observed in adults less than 60 years, participants moving through the peak risk period for hearing impairment over the course of the study.